O studenckich pasjach i zainteresowaniach - projekt Nasze Zajawki = About students` passions and interests - the Nasze Zajawki project - Golonko, Natalia; Olejarz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the concept, course, and partial results of the Nasze Zajawki animation and research project, conducted at the University of Zielona Góra from November 2023 to June 2024. The project was coordinated and implemented by the authors of this study. Its purpose was to explore the interests and passions of students from the "Animacja kultury i twórczej aktywności w sieci" (AKiTAwS) [trans. "Cultural Animation and Creative Online Activity"], followed by the graphic development of collected materials and their regular sharing on program-specific social media channels (Facebook and Instagram).
Keywords: pasja; zainteresowania; studenci; animacja kulturalna; projekt; social media; passion; interests; students; cultural animation; project